Comparative analysis of knowledge bases: ConceptNet vs CYC (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2021)
Data summarization, question answering, text categorization are some of the tasks knowledge bases are used for. A knowledge base (KB) is a computerized compilation of information about the world. They can be useful for complex tasks and problems in NLP and they comprise both entities and relations. We performed an analytical comparison of two knowledge bases which capture a wide variety of common-sense information - ConceptNet and Cyc.Manually curated knowledge base Cyc has invested more than 1,000 man-years over the last two decades building a knowledge base that is meant to capture a wide range of common-sense skills. On the other hand, ConceptNet is a free multilingual knowledge base and crowdsourced knowledge initiative that uses a large number of links to connect commonplace items. When looking for common sense logic and answers to questions, ConceptNet is a great place to start.In this research, two well-known knowledge bases were reviewed - ConceptNet and Cyc - their origin, differences, applications, benefits and disadvantages were covered. The authors hope this paper would be useful for researchers looking for more appropriate knowledge bases for word embedding, word sense disambiguation and natural-language communication.
Keywords: knowledge base, natural language processing, data summarization, question answering, text categorization